2013
DOI: 10.1111/codi.12077
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ventral mesh rectopexy in the management of solitary rectal ulcer syndrome: a cause for optimism?

Abstract: LVMR appears to provide a sustained improvement in QoL, VAS and patient satisfaction in patients with SRUS. Morbidity, recurrence and safety profiles are low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 32 publications
(65 reference statements)
0
50
0
Order By: Relevance
“…the data interpreted within this study, therefore, include patients who have been reported previously by the individual centers. [3][4][5][8][9][10][11][12][13][14][15][16][17] the indication for patients undergoing lVR was at the discretion of individual center practice. however, 4 of the 5 centers included within this study were involved in the creation of a published consensus for lVR with standardized indications for surgery, 18 and, as such, practice was consistent among all of the centers.…”
Section: Methodsmentioning
confidence: 99%
“…the data interpreted within this study, therefore, include patients who have been reported previously by the individual centers. [3][4][5][8][9][10][11][12][13][14][15][16][17] the indication for patients undergoing lVR was at the discretion of individual center practice. however, 4 of the 5 centers included within this study were involved in the creation of a published consensus for lVR with standardized indications for surgery, 18 and, as such, practice was consistent among all of the centers.…”
Section: Methodsmentioning
confidence: 99%
“…29 Similarly studies conducted by Bardek-Amoudi et al and Evan C et al concluded that STARR is more effective in patients with persistent obstructed defecation. 30,31 No recurrence at the end of 4 years was observed in present study while no recurrence at the end of 2 years with minimal complications were reported in study conducted by Palalo B et al 20 The treatment of solitary rectal ulcer syndrome (SRUS) is notoriously difficult because of its chronicity ,complex etiology, clinical presentation and complications. STARR appears to provide a significantly sustained improvement in ODS score and symptomatic relief with minimal, easily manageable complications and none or low recurrence.…”
Section: Discussionmentioning
confidence: 50%
“…This approach is likely to have contributed to the good function experienced by the patients and is consistent with the results of Badrek‐Amoudi et al . using the same surgical approach. We believe that the correction of any persistent posterior compartment prolapse after LVR in patients whose SRUS remains unhealed is necessary to treat continuing obstructive defaecation.…”
Section: Discussionmentioning
confidence: 99%